Management Accounting and Risk management Affecting the Organizational Effectiveness of Small and Medium-Sized Enterprises (SMEs) in Bangkok - สถิตชัยทรัพย์, เสมอขวัญ; กิจรุ่งโรจน์เจริญ, ปรียานุช; เปอร์เขียว, ศศิธร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: (1) examine the levels of opinions regarding management accounting, risk management, and organizational effectiveness of small and medium-sized enterprises (SMEs) in Bangkok; (2) examine the effects of management accounting and risk management on organizational effectiveness.           The sample consisted of 400 accountants working in SMEs in Bangkok, determined using the Yamane (1973) formula at a 95% confidence level. Data were collected using a validated questionnaire and analyzed using descriptive statistics and simple linear regression analysis.           The results indicated that the overall levels of management accounting (x̄= 4.60, S.D. = 0.49) and risk management (x̄= 4.64, S.D. = 0.45) were at the highest level. Organizational effectiveness, including managerial effectiveness (x̄= 4.70, S.D. = 0.45), business success (x̄= 4.70, S.D. = 0.49), and sustainability and competitive advantage (x̄= 4.67, S.D. = 0.47), was also rated at the highest level.           Hypothesis testing revealed that management accounting had a significant positive effect on organizational effectiveness (β = 0.559, p < 0.001, R² = 0.312), while risk management had a stronger significant positive effect (β = 0.623, p < 0.001, R² = 0.389). These findings highlight that both management accounting and risk management play critical roles in enhancing organizational effectiveness, with risk management demonstrating a more prominent influence.